Josef Švejk in the situation of modern novel - Kubíček, Tomáš (Bohemica Olomucensia, 2013)
The paper deals with Hašek's text as the ingenious game with paradoxes. Paradox is reflected here as the compositional and thematical strategy in its formal and ideological aspects. The author describes the Hašek's fictional world not as absurd, but only as world denying the logics that approaches the man as the object only. Švejk as the person is a formulation of conviction that people can preserve their destiny in their own hands face to face with the ruthless mechanism of history.